2012
DOI: 10.1093/aje/kwr418
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Oxidative Stress and Risk of Developing Colorectal Cancer: A Cohort-nested Case-Control Study in the European Prospective Investigation Into Cancer and Nutrition

Abstract: Oxidative stress has been shown to play an important role in carcinogenesis, but prospective evidence for an association between biomarkers of oxidative stress and colorectal cancer (CRC) risk is limited. The authors investigated the association between prediagnostic serum levels of oxidative stress indicators (i.e., reactive oxygen metabolites (ROM) and ferric reducing ability of plasma (FRAP)) and CRC risk. This was examined in a nested case-control study (1,064 CRC cases, 1,064 matched controls) in the Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 22 publications
0
74
1
1
Order By: Relevance
“…This likely indicates a certain degree of reverse causality, possibly caused by the oxidative stress induced by the subclinical cancer as was suggested in the association between ROM and CRC previously within EPIC. 32,36 The associations of dietary b-carotene and vitamins C and E were not ratified by their plasma counterparts. The inconsistency in associations between dietary and plasma measures may exist because biomarkers seem to better reflect internal dose than questionnaire data, which may correlate stronger with lifestyle factors and the intake of other components derived from the dietary questionnaire related to fruit and vegetable consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This likely indicates a certain degree of reverse causality, possibly caused by the oxidative stress induced by the subclinical cancer as was suggested in the association between ROM and CRC previously within EPIC. 32,36 The associations of dietary b-carotene and vitamins C and E were not ratified by their plasma counterparts. The inconsistency in associations between dietary and plasma measures may exist because biomarkers seem to better reflect internal dose than questionnaire data, which may correlate stronger with lifestyle factors and the intake of other components derived from the dietary questionnaire related to fruit and vegetable consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Stratification of the observed associations by geographical region [Scandinavia (Denmark, Norway, Sweden), Central Europe (France, Germany, Netherlands and UK) and Mediterranean (Greece, Italy, Spain)] was performed to determine whether associations were consistent throughout these regions. Additionally, in case-control sets with reactive oxygen metabolites (ROMs) concentration available (488 colon and 290 rectum case-control sets) from a previous study within the EPIC study, 32 observed associations were additionally adjusted for ROM status to examine whether the association could be explained by their antioxidant properties.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…9,13 While nested case-control studies can help minimize this limitation, the concern that oxidative stress may be generated by the preclinical tumor remains. 32 This potential bias can be evaluated by stratifying associations by length of follow-up time, which was rarely done in the identified reports. Another limitation is that breast cancer has been shown to be an etiologically heterogeneous disease, with studies showing modification of known associations by tumor subtype.…”
Section: Biomarkers Of Oxidative Stress and Risk Of Developing Breastmentioning
confidence: 99%
“…20,28 Biomarkers of oxidative stress have been investigated for their association with the development and progression of several cancer types, and in particular breast cancer, as oxidative stress mechanisms may be involved in several known breast cancer risk factors, including obesity and daily alcohol intake, and circulating estrogen levels. [29][30][31][32][33][34] Breast cancer cells have been shown to be susceptible to oxidative damage and have high levels of oxidative stress, including protein damage, DNA damage, and lipid peroxidation. 9,35 Furthermore, several breast cancer risk factors may alter levels of endogenous oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…A faster and cheaper way for the determination of the total antioxidant capacity is to perform only one assay in which all components contribute to an integrating value [2][3][4]. The biomarkers of oxidative stress and antioxidant status are important to assess a physiologically altered state [5], to detect adverse nutritional habits [6] or an increased disease state [7,8].…”
Section: Introductionmentioning
confidence: 99%